Perception and Concerns of Undergraduate Medical Students Toward Research: A Descriptive Cross-Sectional Study - Baloch, Saira; Farhat, Ayesha; Muhammad Riyyan; Kamal; Sajid, Sawaira; Fatima, Manayim; Nazir, Saad; Urwat Ullah; Abdul Hafeez; Kumar, Munesh; Muhammad Mubashir (Indus Journal of Bioscience Research, 2025)
Background: Research engagement is a critical component of medical education, enhancing clinical knowledge, problem-solving skills, and innovation. Despite its importance, undergraduate medical students often face barriers to research participation, including limited time, inadequate mentorship, and insufficient curriculum integration. Objective: To evaluate the perceptions, awareness, and barriers faced by undergraduate medical students toward research and to identify actionable strategies to improve their engagement. Methods: A descriptive cross-sectional study was conducted among 70 undergraduate students at Bilawal Medical College, Pakistan, between September and November 2022. Data were collected using a structured, validated questionnaire distributed during lecture sessions. Variables included perceptions of research benefits, career aspirations, awareness of funding agencies, and barriers to participation. Data were analyzed using SPSS version 25, with results presented as frequencies, percentages, and associations using chi-square tests. Results: The mean age of participants was 22.52 years (SD = 2.95). Most students (67.1%) believed research was beneficial, and 52.9% recognized its role in clinical knowledge. However, only 24.3% viewed research as a future career option, and 15.7% were aware of funding agencies. Major barriers included lack of motivation and knowledge (51.4%) and curriculum integration (21.4%). Significant associations were found between funding awareness and perceived importance of research (χ² = 6.43, p = 0.01). Conclusion: Medical students value research but face significant barriers, including limited awareness and institutional support. Integrating structured research training and mentorship into the curriculum is essential to foster a research-oriented culture in medical education.